Dampak Kotak Infaq Nahdlatul Ulama (KOIN NU) terhadap Kesejahteraan Masyarakat Batanghari Lampung Timur - Fauziah, Habibatul (Maliyah : Jurnal Hukum Bisnis Islam, 2024)
East Lampung BPS data shows an increase in the number of poor people by 6,220 people in 2021. So solutions are needed to overcome poverty. One of them is through zakat, infaq and alms amil institutions through the Nahdlatul Ulama Infaq Box movement program (KOIN NU) where activities consist of collecting, managing and distributing infaq funds and alms which are shown to people in need. This research aims to examine the management of KOIN NU funds and its impact on the welfare of the Batanghari community. This research is descriptive qualitative, namely research that utilizes qualitative data and then explains it descriptively. The data sources in this research use primary data sources and secondary data sources using data collection techniques through interviews and documentation. The research results show that the KOIN NU program has succeeded in collecting funds through 12,353 infaq boxes which were distributed to the Batanghari community. Even though the use of funds is still consumptive in nature, this program has had a positive impact on community welfare, especially in meeting daily needs. However, the long-term program has not been implemented because there are several obstacles such as suboptimal use of funds and a lack of human resources.